“PENGARUH LATIHAN BOX JUMP TERHADAP POWER OTOT TUNGKAI PADA TIM BOLA VOLI PUTRA MAN 1 BENGKALIS” - Aliasir Fahmi; Slamet Slamet; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstark: The problem in this study is that the Smash does not cross the net with a height of 2.55 meters and can easily be blocked by opponents. Likewise, when easily blocking, the opponents set up the ball without any obstacles. The title of this research is "the effect of box spring training on leg muscle strength in the MAN 1 volleyball team MAN 1 Bengkalis" so that athletes can perform and play much better in the future, especially after researching and finding out if there is an increase in their power speed of the athlete in the volleyball game to keep track of the opponent's game and to achieve maximum results in the future. The form of this study is (using a pre-test post-test design approach in one group) with a population of MAN 1 Bengkalis team. The data in this study is the entire population of 10 people. The instrument used in this research was to use a vertical jump test, which aims to determine the effect of box spring training on leg muscle strength. The data is then statistically processed to test normality using the lilifours test at a significant level of 0.05α. Based on the analysis of normality test data, X produces a LoMax of 0.138 and an Ltable of 0.258, which means LoMax <Ltable. while Y produces variable LoMax of 0.133 and Ltable of 0.258. This means that LoMax <L table data is normally distributed. So it can be concluded that for the effect of the variable x with the variable y obtained the value of t = 4.777 then tcount> ttable (4.777)> (1.833), then Ha is accepted, in other words there is a significant effect on the exercise of influence of the box jump exercise on power limb muscles of the MAN 1 volleyball team Bengkalis team for men.Key Words: Box Jump Exercise, Leg Muscle Power